Ceratozetes mediocris Berlese 1908 - Behan-Pelletier, Valerie M.; Lindo, Zoë (Zenodo, 2019)
Ceratozetes mediocris Berlese, 1908 Geographic Location : AB : Kananaskis Country (Mitchell 1978); Cypress Hills PP, 3 mi. S. Elkwater (Behan-Pelletier 1984); Waterton Lakes NP; Writing-on-Stone PP; Cypress Hills PP (Behan-Pelletier & Eamer 2009); ABMI Sites (Walter et al. 2014); SK : Battlefords PP; Moose Mt. PP; Prince Albert NP; Cypress Hills PP, Loch Lomond; Duck Lake PP (Behan-Pelletier 1984); Saskatoon National Grasslands (Behan-Pelletier & Eamer 2009); MB : Spruce Woods PP; Riding Mt. NP (Behan-Pelletier 1984); ON : St. Lawrence Islands NP: Grenadier Is.; McDonald Is.; Thwartway Is.; Backus Woods Conservation Area, 4 mi N. Port Rowan; Long Point NWA: Courtright Ridge; Squire's Ridge; Little Creek Ridges; Rondeau PP; Pt. Pelee NP; 6 mi. W. Richmond (Behan-Pelletier 1984); Petawawa National Forestry Institute, Chalk River (Bird & Chatarpaul 1986); Sudbury (St. John et al. 2002); Shaw Woods Nature Preserve; Otter Lake; A'nowaghi Forest and Wetland (Behan-Pelletier & Eamer 2009); n ear Chapleau (Rousseau et al. 2018); QC : Stanstead Co., Amy Rd., 0.5 km N. Jack Cold Rd; Gatineau Park (Behan-Pelletier 1984); Morgan Arboretum (Behan-Pelletier 1984, Behan-Pelletier & Eamer 2009; Sylvain & Buddle 2010); NB : Kouchibouguac NP (Behan-Pelletier 1984); NS : Cape Breton Highlands NP (Behan-Pelletier 2010; Behan- Pelletier et al. 1987). Habitats : AB : mixed prairie; fescue grassland; aspen forest; kinnikinnick mat and soil; mixed coniferhardwood forest; slough in maple oak parkland; grass litter in black-oak, maple woodland; Lirodendron tulipifera litter; Quercus and mixed deciduous litter; Thuja swamp; White spruce, White birch and Trembling aspen litter; sphagnum. Distribution : Semicosmopolitan. : Published as part of Behan-Pelletier, Valerie M. & Lindo, Zoë, 2019, Checklist of oribatid mites (Acari: Oribatida) of Canada and Alaska, pp. 1-180 in Zootaxa 4666 (1) on page 132, DOI: 10.11646/zootaxa.4666.1.1, http://zenodo.org/record/4000595 : {"references": ["Berlese, A. (1908) Elenco di generi e specie nouve di acari. Redia, 5, 1 - 16.", "Mitchell, M. J. (1978) Vertical and horizontal distribution of oribatid mites (Acari: Cryptostigmata) in an aspen woodland soil. Ecology, 59 (3), 516 - 525. https: // doi. org / 10.2307 / 1936582", "Behan-Pelletier, V. M. (1984) Ceratozetes (Acari: Ceratozetidae) of Canada and Alaska. The Canadian Entomologist, 116, 1449 - 1517. https: // doi. org / 10.4039 / Ent 1161449 - 11", "Behan-Pelletier, V. M. & Eamer, B. (2009) Ceratozetes and Ceratozetoides (Acari: Oribatida: Ceratozetidae) of North America. The Canadian Entomologist, 141, 246 - 308. https: // doi. org / 10.4039 / n 09 - 023", "Walter, D. E., Latonas, S., Byers, K. & Lumley, L. M. (2014) Almanac of Alberta Oribatida Part I. Ver. 2.4. Royal Alberta Museum, Edmonton, AB. 542 pp. Available from: https: // www. royalalbertamuseum. ca / research / lifeSciences / invertebrateZoology / research. cfm (accessed 20 March 2019)", "Bird, G. A. & Chatarpaul, I. (1986) Effect of whole-tree and conventional forest harvest on soil microarthropods. Canadian Journal of Zoology, 64, 1986 - 1993. https: // doi. org / 10.1139 / z 86 - 299", "St. John, M. G., Bagatto, G., Behan-Pelletier, V. M., Lindquist, E. E., Shorthouse, J. D. & Smith, I. M. (2002) Mite (Acari) colonization of vegetated mine tailings near Sudbury, Ontario, Canada. Plant and Soil, 245, 295 - 305. https: // doi. org / 10.1023 / A: 1020453912401", "Rousseau, L., Venier, L., Hazlett, P., Fleming, R., Morris, D. & Handa, I. T. (2018) Forest floor mesofauna communities respond to a gradient of biomass removal and soil disturbance in a boreal Jack pine (Pinus banksiana) stand of northeastern Ontario (Canada). Forest Ecology and Management, 407, 155 - 165. https: // doi. org / 10.1016 / j. foreco. 2017.08.054", "Sylvain, Z. A. & Buddle, C. M. (2010) Effects of forest stand type on oribatid mite (Acari: Oribatida) assemblages in a southwestern Quebec forest. Pedobiologia, 53, 321 - 325. https: // doi. org / 10.1016 / j. pedobi. 2010.03.001"]}